Crossover study of proportional assist versus assist control ventilation. Issue 1 (28th May 2014) - Bhat, Prashanth; Patel, Deena-Shefali; Hannam, Simon; Rafferty, Gerrard F; Peacock, Janet L; Milner, Anthony D; Greenough, Anne
Abstract : Objective: To test the hypothesis that in very prematurely born infants remaining ventilated beyond the first week, proportional assist ventilation (PAV) compared with assist control ventilation (ACV) would be associated with reduced work of breathing, increased respiratory muscle strength and less ventilator–infant asynchrony which would be associated with improved oxygenation. Design: Randomised crossover study. Setting: Tertiary neonatal unit. Patients: 12 infants with a median gestational age of 25 (range 24–26) weeks were studied at a median of 43 (range 8–86) days. Interventions: Infants were studied for 1 h each on PAV and ACV in random order. Main outcome measures: At the end of each hour, the work of breathing (assessed by measuring the diaphragmatic pressure time product), thoracoabdominal asynchrony and respiratory muscle strength (maximal inspiratory pressure, maximal expiratory pressure (Pemax) and maximal transdiaphragmatic pressure (Pdimax)) were assessed. Blood gas analysis was performed and the oxygenation index (OI) calculated. Results: After 1 h on PAV compared with 1 h on ACV, the median OI (5.55 (range 5–11) vs 10.10 (range 7–16), p=0.002) and PTP levels were lower (217 (range 59–556) cm H2 O.s/min vs 309 (range 55–544) cm H2 O.s/min, p=0.005), while Pdimax (44.26 (range 21–66) cm H2 O vs 37.9 (range 19–45) cm H2 O, p=0.002) and Pemax (25.6 (range 6.5–42) cm H2 O vs 15.9 (range 3–35) cm H2 O levels p=0.010) were higher. Conclusions: These results suggest that PAV compared with ACV may have physiological advantages for prematurely born infants who remain ventilated after the first week after birth.